Effectiveness of specific professional training in male elite adolescent team handball players - Wagner, H.; Hinz, M.; Radic, V. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In male team handball, the professional training of adolescent players in elite team handball academies is a crucial element for becoming a top-elite player. Professional training at this age often consists of 7-8 sessions per week, which include both physical and team handball-specific training, as well as 1-2 national or international top-level matches. Despite the frequency and intensity of this training, its effectiveness is often assessed through coach observations during training and matches, as well as general physical performance tests. However, the direct influence of this professional training on specific physical performance in team handball is unknown, despite its importance as a criterion for effective training in adolescent elite team handball. Consequently, the aims of the study were (1) to provide professional training to elite adolescent team handball players, and (2) to measure their performance improvement utilizing a team handball specific performance test. METHODS: Thirty adolescent elite male team handball players, including six goalkeepers and 24 field players, participated in an eleven-week training program. This program included the pre-season preparation phase (eight weeks) and the initial three games of the highest German Team Handball Leagues official season (three weeks). The training program included 2-3 physical sessions, 4-5 specific team handball sessions, totaling 7-8 training sessions per week, and 1-2 matches weekly. Inclusion criteria for field players encompassed completing at least 80% of all training sessions. Consequently, the study comprised nine under-19 players (age: 17.2 ± 1.3 years, body weight: 77.8 ± 6.0 kg, body height: 1.82 ± 0.04m) and nine under-17 players (age: 15.6 ± 0.9 years, body weight: 71.5 ± 14.5 kg, body height: 1.82 ± 0.06m). All participants performed the team handball game-based performance test twice (pre- and post-testing). A paired sample t-test was used to compare the difference in performance between the pre- and post-tests of both under-19 and under-17 players. RESULTS: Significant differences (P < 0.05) were observed in the defense and offense time in the game-based performance test and body weight for both under-19 and under-17 players. Furthermore, among the under-17 players, additional significant differences were noted in peak oxygen uptake, fast break time, as well as ball velocity and jump height in the jump shot. CONCLUSION: As expected, team handball specific agility in defense and offense improved for both under-19 (+3%) and under-17 (+6%) players, which was one of the training programs main aims. However, for the under-17 players the massive increase in peak oxygen uptake (+16%) as well as ball velocity (+7%) and jump height (+20%) in the jump shot was unexpected. We suggest that professional and targeted specific training in this age has a significant impact on the long-term development of adolescent team handball players and is the basis for a professional handball career.